Effect of Whole or Ground Flaxseed Supplementation on Fatty Acid Profile, Fermentation, and Bacterial Composition in Rumen of Dairy Cows - Huang, Guoxin; Guo, Liya; Chang, Xiaofeng; Liu, Kaizhen; Tang, Wenhao; Zheng, Nan; Zhao, Shengguo; Zhang, Yangdong; Wang, Jiaqi (Frontiers in Microbiology, 2021)
Flaxseed is rich in α-linolenic acid (ALA) and can increase omega-3 polyunsaturated fatty acid in the milk of dairy cows. However, the response of rumen fermentation to different forms of flaxseed supplementation is unknown. This study aimed to investigate the effect of different forms of flaxseed on the fatty acid profile, fermentation, and composition of bacteria in the rumen of dairy cows. Thirty Holstein dairy cows were selected and divided randomly into 3 groups. Cows were fed a basal diet (control check; CK) or basal diets supplemented with either 1,500 g per day whole flaxseed (WF) or 1,500 g per day ground flaxseed (GF). The WF group had the highest ALA content in rumen fluid, whereas no difference was found between the CK and GF groups. However, the molar proportion of acetate increased in the WF and GF groups and was the highest in the GF group, and a similar trend was shown by propionate, isobutyrate, butyrate, isovalerate, and valerate (CK < WF < GF). The abundance of Ruminococcaceae_NK4A214_group, Christensenellaceae_R-7_group, and Eubacterium_coprostanoligenes_group also showed the same trend (CK < WF < GF). Different forms of flaxseed released ALA into the rumen differently, and the molar proportion of volatile fatty acids and composition of bacteria were influenced mainly by the amount of ALA released into the rumen.